Valle del Cauca’s horticultural production: an export alternative and post-conflict strategy for region - Tapiero Cuellar, Jose Libardo (Revista Colombiana de Investigaciones Agroindustriales, 2017)
Valle del Cauca’s horticultural production: an export alternative and post-conflict strategy for region The Valle del Cauca department is a production potential territory in, consumption and agroindustrial transformation of fruit trees, with good soils, varied climates and different varieties of fruits. Likewise is located in a technological corridor integrated by universities, research centers and scientific-technological research groups allows to close the gaps between producers, traders and transformation-export companies. The production of the fruit and vegetable sector in the valle del Cauca is around 600,000 tons per year for citrus, pineapple, papaya, grape, guava, plantain and mango. According to the Departmental Secretariat the vegetables sector participates with 76,000 tons, making it the second national producer for the chain. The vegetable per capita consumption recommended by the World Health Organization - WHO is 400 g against 200 g for Colombia becoming an important opportunity to producers and traders in the region. With end of 50 years of armed conflict and signing of peace process in the country; where victims were recognized, weapons were left, and reintegration into civilian life of ex-combatants was carried out, resulting in generation of constitutional, economic, and social reform projects where agroindustrial sector stands out as an excellent option in the framework of the production and transformation of fruit trees in Valle del Cauca. Currently, several productive-sector regional companies export mango and citrus to European destinations and pineapple to nort America. For this reason, it is necessary strengthen the cluster or productive chain that allows the sector’s momentum. Likewise, it should invest in processing companies specialized in the post-harvest management handling of fruits and vegetables, integrated to research centers in bio package and agroindustrial transformation that allow to diminish the losses after department horticultural production. This territory has a high potential in citrus fruits, Hass avocado, strawberry, melon, papaya, pineapple, lulo and coconut among others, which can be increased by a high quality chain integration as Chile and Costa Rica have done. One of the fruits offers a high potential of work and research that is in the horticultural bet is blackberry (Rubus glaucus), where institutions such as, Asofrunidos, El Sena-Centro agropecuario de Buga (CAB) and El Sena-Centro Nacional de Asistencia Tecnica a la Industria (ASTIN), have made advances in production and research of the country’s blackberrie exports in upper region of municipality of Ginebra, through organic fruits and greater resistance to mechanical impact. Also, the design of an intelligent bio-package that allows exporting blackberries per individual consumption is carrying out. The other way, CAB and Universidad Nacional de Colombia Palmira venue are investigating in pollination processes assisted by bees of the genus Apis mellifera, which improves the production, quality and size of the fruit.